Balanço hídrico e da salinidade do solo na bananeira irrigada com água de diferentes salinidades - Gondim, Ancélio Ricardo de Oliveira [UNESP]; Medeiros, José Francismar de; Levien, Sérgio Luís Aguilar; Carmo, Gilcimar Alves do; Senhor, Rosemberg Ferreira (Editora da Universidade Estadual de Maringá (EDUEM), 2009)
O objetivo deste trabalho foi avaliar o efeito de diferentes níveis de salinidade de água de irrigação no uso consultivo na fase reprodutiva da bananeira e evolução da salinidade do solo. Adotou-se o delineamento inteiramente casualizado em parcelas subdivididas, totalizando oito tratamentos com quatro repetições por tratamento. Os níveis de salinidade foram obtidos a partir de águas naturais de poços dos aquíferos arenito e calcário e foram misturadas em tanques de alvenaria para a obtenção das concentrações de salinidade desejada. Verificou-se que a área do bulbo com umidade superior a 8% representa aproximadamente 50% do volume do solo. A evapotranspiração da cultura diminuiu com o aumento da salinidade entre os tratamentos, o kc médio no período variou de 1,01 a 1,09 em águas de salinidade extremas. Comparando os perfis da salinidade do solo, verificou-se que a concentração de sais foi superior na camada superficial aos 440 dias após plantio.

The objective this work was to evaluate the advisory use of two cultivars banana and the salinity of the soil in different water salinity levels (0.55; 1.70; 2.85; and 4.00 dS m-1) during the reproductive phase. The experimental design chosen was randomized complete blocks in subdivided plots, totaling eight treatments with four repetitions per treatment. The salinity levels were obtained from natural waters of wells from sandstone and calcareous aquifers and were mixed in masonry tanks in order to obtain the desired salinity concentrations. It was verified that the area of the bulb with moisture greater than 8% represents approximately 50% of the volume of the soil. The evapotranspiration of the culture decreased with the increase in the salinity among the treatments; the average kc in the period varied from 1.01 to 1.09 in waters of extreme salinity. Comparing the salinity profiles of the soil, it was verified that the concentration of salts was highest on the surface layer at 440 days.
Soil water and salinity balance on banana irrigated with water of varied salinity
Keywords: banana culture; salinity; Irrigation; bananicultura; salinização; Irrigação